Evaluation of the Endomysial Antibody for Celiac Disease: Operating Properties and Associated Cost Implications in Clinical Practice. (1st December 1997) - Atkinson, Kenneth; Tokmakajian, Sonya; Watson, William; Gregor, James
Abstract : OBJECTIVE: To evaluate the operating properties of endomysial antibodies (EMAs) in the diagnosis of celiac disease and to examine, using a cost minimization model, different strategies used in the diagnosis of celiac disease. METHODS: A total of 248 EMA results were reviewed and compared with small bowel biopsy results in 66 patients who had undergone both tests. Regression analysis was used to look for predictors of positive EMA results and positive biopsy results. A cost minimization model from a societal perspective was used to evaluate the cost differences among three different strategies. RESULTS: EMAs had a sensitivity of 95% and specificity of 64%. The only predictor of a positive biopsy result that reached statistical significance was a positive EMA. The strategy of EMA as a diagnostic test for celiac disease was the most expensive strategy, with a cost of 3, 174 per patient assessed. The strategy of small bowel biopsy for all patients had a cost of 997, and a strategy of EMA followed by small bowel biopsy for positive patients had a cost of 866 per patient. The results were sensitive to cost of a gluten-free diet, the specificity of the EMA and the cost of a small bowel biopsy. CONCLUSION: The EMA is best used as a screening test from both a clinical and cost perspective.